ANALISIS PENGETAHUAN MAHASISWA KEPERAWATAN TERHADAP LANSIA DAN MINAT KERJA DI PELAYANAN HOME CARE - Antia, Antia (Indonesian Journal of Nursing Health Science, 2016)
Abstract The changing population structure has many implications for the elderly. Health care is significantly in need of more gerontologically trainer to addresss the complex health care needs of its older citizens. Nurses play an essential role in the provision of acute and chronic care, health education, and health promotion for these older people. Nursing students who plan to be care providers. They could have a lack of knowledge of elderly people that influence their will anxious dan have pressure in care. Good education programs designs to gerontology and Home care could influence willingness to care for or intention to work with them. Analyzing correlation between nursing studentsâ knowledge toward elderly people and intent to work in home care with the elderly. There have correlation between nursing studentsâ knowledge toward elderly people and intent to work in home care with the elderly. Respondents are students of Nursing Programme Health sciences Faculty University of Esa Unggul in level of two, four, six and eight. A descriptive corelational study will used via self reported questionnaire. Three part of questionnaire, first part about respondent characteristic, second part about knowledge of elderly and last part about intent to work. Performed analyzed using Chi Square test with p=0,156 (p>Î±) that means no correlation between nursing studentsâ knowledge toward elderly people and intent to work in home care.Keywords: intent to work, knowledge of elderly, nursing student